2010
DOI: 10.1111/j.1365-2648.2010.05304.x
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum infusion to promote nursing student well‐being

Abstract: In light of the increasing rigour of baccalaureate nursing programmes, it is important for educators to be aware of the health-related effects of stress and isolation on students. By increasing student self-awareness and changing relational dynamics in the classroom, student well-being can be supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…Research identified the most effective methods of stress management in this population as: 1) relaxation techniques, 2) meditation, and 3) positive coping methods (Gibbons, 2010;Jones and Johnston, 2006;Peterson et al, 2008;Yearwood & Riley, 2010). The purpose of this study was to develop a stress management education session for MSN students enrolled in their initial graduate level clinical rotations during the spring semester of 2016 at RIC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Research identified the most effective methods of stress management in this population as: 1) relaxation techniques, 2) meditation, and 3) positive coping methods (Gibbons, 2010;Jones and Johnston, 2006;Peterson et al, 2008;Yearwood & Riley, 2010). The purpose of this study was to develop a stress management education session for MSN students enrolled in their initial graduate level clinical rotations during the spring semester of 2016 at RIC.…”
Section: Discussionmentioning
confidence: 99%
“…These studies identified the most effective methods of stress management in nursing students as: 1) relaxation techniques, 2) meditation, and 3) using positive coping methods (Gibbons, 2010;Jones & Johnston, 2006;Peterson et al, 2008;Yearwood & Riley, 2010).…”
Section: Stress Management and Coping Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Activities of self-reflection about common health and well-being issues identified issues of isolation, shock and anger, use of campus mental health, valuing educators as a source of support [34]. Survey results reported by Baxter et al [35] reported approximately 27% of health-related information (e.g.…”
Section: Health Seeking Behaviorsmentioning
confidence: 99%